High‐temperature properties and failure mechanism of 3D six‐directional braided composites under out‐of‐plane compression. Issue 6 (7th February 2020) - Han, Wen‐Fen; Li, Dian‐Sen; Jiang, Lei
Abstract: Three‐dimensional (3D) six‐directional braided carbon/epoxy composites with different braiding angles were fabricated successfully. The effect of braiding angles and temperature on mechanical properties and failure mechanism were analyzed. The results show that the braiding angle and temperature both have a significant effect. As braiding angle increases, out‐of‐plane compression stress vs strain curve increases and the compression properties improve. At high temperatures, the stress vs strain curves are non‐linear up and the compression properties reduce. Besides, the out‐of‐plane performances of 3D six‐directional braided composite at room and high temperatures are more excellent than 3D four‐directional and five‐directional braided composites. Under out‐of‐plane compression, at room temperature, the materials appear 45° shear fracture; the phenomenon of fibers shear fracture and extraction is more distinct with larger braiding angle; the main failure is the fiber bundles expand outward and the matrix cracks. At high temperatures, the materials exhibit ±45° shear cracks; composites are compressed flat and expand along the transverse direction; the main failure is the matrix softening and exfoliation from the fiber bundles, the fiber/matrix interface debonds seriously.